Accumulated dose stability parameters in p-type and n-type silicon diodes - Kelly Pascoalino; Josemary A. C. Gonçalves; Fabio de Camargo; Carmen C. Bueno (Brazilian Journal of Radiation Sciences, 2025)
This work investigates the influence of doping type on the dose responses and the accumulated dose stability of n- and p-type silicon MCz diodes. The operating principle of diode-based dosimeters relies on measuring the radiation-induced currents delivered by non-polarized diodes throughout the exposure time. An electrometer promptly reads the current signal, linearly dose rate dependent. The offline integration of the current signal provides the charge generated in the sensitive volume of the diode, expected to be proportional to the absorbed dose. The experimental approach involves analyzing the repeatability of the current signals, the dose responses of both pristine and pre-irradiated diodes, the correspondent charge sensitivities, and the sensitivity decay with increasing doses. For doses up to 175 kGy, the results reveal a linear dose response of the MCz(p) diode, characterized by a charge sensitivity of 3.1 µC/Gy.  Within the same dose range, the response of the MCz(n) diode is visibly saturated and given by a fourth-order polynomial function. This saturation effect is likely linked to radiation damage effects manifesting in the current decay with increasing accumulated doses. This surmise is confirmed in this work by a less pronounced drop in sensitivity of the p-type diode than that recorded for the n-type diode when both are subjected to 175 kGy. This behavior is ascribed to the working principle of the diode in the short-circuit current mode and the differences between the diffusion lengths of minority carriers in n- and p-type silicon materials. The diodes' response stability and dose lifespan remain to be further investigated.